2021
DOI: 10.3390/ijms22115987
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Structural Imaging Provides 3D Organization of 46 Chromosomes of a Human Lymphocyte Prophase Nucleus

Abstract: Three dimensional (3D) ultra-structural imaging is an important tool for unraveling the organizational structure of individual chromosomes at various stages of the cell cycle. Performing hitherto uninvestigated ultra-structural analysis of the human genome at prophase, we used serial block-face scanning electron microscopy (SBFSEM) to understand chromosomal architectural organization within 3D nuclear space. Acquired images allowed us to segment, reconstruct, and extract quantitative 3D structural information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…To enable comparison with current understandings of the mitotic chromosome, it is critical to determine the DNA content of the MNDs. To this end, we utilized a topographic technique frequently used to determine the volumes of biomolecular structures, AFM, to quantify the physical volume of the MNDs, and used the DNA density determined in previous SBFSEM studies , to quantify the DNA content within the MNDs. We confirmed that the unperturbed (not extended) mitotic chromosome imaged by AFM consists of granular structures (CGs) that are roughly 100 to 200 nm in diameter (median 153 ± 19 nm), consistent with the 3D-SIM and BALM results described above, even with any potential contribution of tip broadening in these measurements (see Materials and Methods; Figures S7A,B and S8).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To enable comparison with current understandings of the mitotic chromosome, it is critical to determine the DNA content of the MNDs. To this end, we utilized a topographic technique frequently used to determine the volumes of biomolecular structures, AFM, to quantify the physical volume of the MNDs, and used the DNA density determined in previous SBFSEM studies , to quantify the DNA content within the MNDs. We confirmed that the unperturbed (not extended) mitotic chromosome imaged by AFM consists of granular structures (CGs) that are roughly 100 to 200 nm in diameter (median 153 ± 19 nm), consistent with the 3D-SIM and BALM results described above, even with any potential contribution of tip broadening in these measurements (see Materials and Methods; Figures S7A,B and S8).…”
Section: Resultsmentioning
confidence: 99%
“…From these topographic AFM images, we determined the volume of each MND and, with the DNA density measured by SBFSEM (5.8 nm 3 /bp), , found that most domains encompass between 20 kb and 200 kb DNA, with a median content of 76 kb (Figure D). This amount of DNA is quite similar to the predicted size of the inner chromatin loops (80 kb) of the recent nested loop model .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations